Responses to supplementation in White Fulani cattle under agro-pastoral management in northern Nigeria. II. Fodder - Campbell, D.A.; Ikuegbu, O.A.; Owen, E.; Little, D.A. (Springer, 1996)
The effect of dry-season supplementation of White Fulani cattle in northern Nigeria with legume standing hay (fodderbanks) was investigated. Over 430 cattle were recorded in 8 herds over 2-5 years. Fodder bank supplementation may have reduced weight losses in calves and breeding females during the dry-season. Emergency sales of immature animals were lower on fodder banks (6.5 percent vs 14.3 percent, P<0.01). There was no evidence that fodder banks may have had a deleterious effect by encouraging dry-season. Fodder banks may have had a deleterious effect by encouraging dry-season conceptions. Resulting dry season calvings led to calving percentages of 36.9 percent on fodder and 60.3 percnet on no fodder (P<0.05). Calf mortality was also higher on fodder banks; animals not reaching their second year were 13 percent on fodder bank vs 3.9 percent on no fodder (P<0.01). It was concluded that dry season nutrition interaction with the agro-pastoralist livestock system needs further investigation.